Essays and addresses toward a liberal education - Baird, Albert Craig 1883- (Boston Ginn and company, 1934)
"The present anthology ... attempts to set forth significant point of view in various fields of thinking - educational, philosophical, aesthetic, moral and religious, political, national and international, economic and social."--Introductory note.
Introductory: On writing and speaking -- [1.] The educational approach -- [2.] The psychological, aesthetic, and philosophical approach -- [3.] The moral and religious approach -- [4.] The literary approach -- [5.] The biographical approach -- [6.] The scientific approach -- [7.] The national and political approach -- [8.] The international approach -- [9.] The economic and social approach.
Includes bibliographical references (pages 416-422) and index.
Keywords: Essays; Literature -- Collections